Constructing high-performance radiation-resistant ternary YSZ-MgO-CNT nanocomposites via tailored nanostructures. Issue 10 (August 2021) - Tang, Jun; Cheng, Tao; Wang, Yongqiang; Hu, Lulu; Hong, Mengqing; Qin, Wenjing; Cai, Guangxu; Jiang, Changzhong; Ren, Feng
Graphical abstract: Highlights: Bulk nanostructured ceramic was prepared by embedding CNTs in YSZ-MgO nanocrystals. He ion irradiation response of CNT-reinforced ceramic at 500 °C was studied. Management of defects/He atoms via constructed ternary nanostructures was realized. High ability in keeping microstructure stability and resisting radiation hardening. Abstract: Developing long-lifetime bulk-form ceramic-based materials with high irradiation resistance is crucial for advanced nuclear systems. Here, we incorporated carbon nanotubes (CNTs) into yttria-stabilized zirconia (YSZ) and magnesia (MgO) nanocrystals to fabricate bulk YSZ-MgO-CNT nanocomposites with abundant ternary nanostructures by spark plasma sintering. To understand the role of tailored ternary nanostructure on irradiation, we investigated the microstructure and mechanical properties evolutions of the YSZ-MgO-CNT nanocomposites irradiated by multi-energy He + ions at high temperature to different fluences. Compared with the single-phase YSZ and ultrafine-grained YSZ-MgO composites, the YSZ-MgO-CNT nanocomposites possessed higher ability to manage irradiation-induced He bubbles/defects via the defect-interface interactions of proposed "loading-unloading" and "loading-transporting-unloading" mechanisms for controlling the dynamical behaviors of He atoms/defects in the CNT-doped ternary nanostructures, thereby presenting more stable microstructure and better performance in resisting irradiation hardening. This work provides insight into the design of advanced inert matrix nuclear fuel and new nuclear waste management materials.